2021
DOI: 10.1093/oxfimm/iqab002
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal immune responses in COVID19 - a living review

Abstract: COVID-19 was initially characterised as a disease primarily of the lungs, but it is becoming increasingly clear that the SARS-CoV2 virus is able to infect many organs and cause a broad pathological response. The primary infection site is likely to be a mucosal surface, mainly the lungs or the intestine, where epithelial cells can be infected with virus. Whilst it is clear that virus within the lungs can cause severe pathology, driven by an exaggerated immune response, infection within the intestine generally s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…This hypothesis is supported by the following finding: SARS-CoV-2 can cause severe pathology in the lungs driven by an exaggerated immune response, whereas infection in the intestine generally seems to cause minor or no symptoms [5,[18][19]. Nonetheless, the results of a meta-analysis of the prevalence and mortality of COVID-19 patients with gastrointestinal symptoms indicate that the mortality among patients with gastrointestinal symptoms is similar to the overall mortality [20].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This hypothesis is supported by the following finding: SARS-CoV-2 can cause severe pathology in the lungs driven by an exaggerated immune response, whereas infection in the intestine generally seems to cause minor or no symptoms [5,[18][19]. Nonetheless, the results of a meta-analysis of the prevalence and mortality of COVID-19 patients with gastrointestinal symptoms indicate that the mortality among patients with gastrointestinal symptoms is similar to the overall mortality [20].…”
Section: Discussionmentioning
confidence: 89%
“…Determining the SARS-CoV-2 viral RNA sequence in these countries for individuals suffering solely from gastrointestinal symptoms will allow clarification of whether there is a mutation that improves the effectiveness of the fecal-oral infection pathway. Because the microbiome is a key part of the intestinal mucosal barrier sites and plays a major role in shaping the immune system, it may also play an important role in infection by SARS-CoV-2 and subsequent immune responses [ 5 , 13 , 28 ]. It is therefore suggested that the intestinal microbiome of asymptomatic and symptomatic individuals should be analyzed and compared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They comprise innate-like T cells ( e.g ., invariant natural killer T, innate lymphoid cells, and γδ T cells) involved in pulmonary mucosal antiviral immunity and tissue protection and repair after resolving the infection[ 43 ]. Pearson et al [ 44 ] focused on local mucosal responses during viral infection, particularly with SARS-CoV-2 in both lungs and gut. They found that IL-33 and IL-8 were increased in fecal samples of COVID-19 patients due to intestinal involvement[ 44 , 45 ].…”
Section: Sars-cov-2 and Mucosal Immunity Of The Gimentioning
confidence: 99%
“…Pearson et al [ 44 ] focused on local mucosal responses during viral infection, particularly with SARS-CoV-2 in both lungs and gut. They found that IL-33 and IL-8 were increased in fecal samples of COVID-19 patients due to intestinal involvement[ 44 , 45 ]. Simultaneously, cytokines such as IL-1b, tumor necrosis factor alpha, and IL-6 were found to decrease.…”
Section: Sars-cov-2 and Mucosal Immunity Of The Gimentioning
confidence: 99%